THE ROLE OF THE PEOPLE IN POST LEGISLATIVE SCRUTINY: PERSPECTIVES FROM MALAYSIA AND AUSTRALIA - Sarah Petronella Moulds; Ying Hooi (Journal of International Studies, 2020)
The purpose of this article is to critically examine the role of the people in the process of reviewing the implementation and effectiveness of existing laws, described in the emerging literature as ‘post-legislative scrutiny or ‘PLS’. Examining the options for citizen engagement with legislative review is critical for all parliamentary democracies grappling with the challenge of rebuilding trust between citizens and institutions. This is because reviewing the content and purpose of proposed and the implementation and impact of existing laws is a way for parliamentarians to give effect to their democratic promise. The methodology employed is qualitative in nature with a tiered approached to identifying and examining the extent to which individuals and non-government actors can contribute to parliamentary review processes in two Westminster-inspired parliamentary democracies: Australia and Malaysia. Using case study examples and examining both structural and cultural features of the systems of legislative review in both systems, this article directly challenges some of the assumptions previously associated with PLS in the existing literature. Experiences of different ‘ad hoc’ forms of PLS in both Australia and Malaysia suggest that there could be substantial benefits for lawmakers and citizens by moving toward a more deliberative, ‘bottom up’ approach to PLS in the future.